Enhancing the physical fitness of young men through the practice of martial arts - Tashchiyan A.A.; Zhikharev D.A.; Lobanova E.N.; Chub S.A. (Theory and Practice of Physical Culture, 2025)
Objective of the study was to create and empirically evaluate the efficacy of a series of exercises designed to enhance the physical abilities of young males in grades 10-11 through the use of martial arts in the school’s physical education curriculum. Methods and structure of the study. The research project was conducted at St. George Secondary School in Rostov-on-Don from October 1, 2023, to May 20, 2024. Ten young men participated in the study, with five assigned to the control group and the same number to the experimental group. The research methods employed included a review of scientific and educational literature, pedagogical observation, testing, a pedagogical experiment, and statistical analysis. Results and conclusions. The outcomes of the experiment revealed that the performance of the experimental group in the test trials was significantly superior in almost all aspects compared to the control group. This suggests that the compiled set of physical exercises proved to be highly effective and efficient, outperforming traditional basic exercises and games aimed at enhancing physical qualities in the context of physical education for young men in grades 10-11. Based on the findings, it appears advisable to recommend the hand-to-hand combat exercise complexes developed and employed in the research work, particularly for the initial stage of training, as a more effective approach to addressing physical education objectives for high school students.